Scarce, abundant, or ample? A time-varying model of the reserve demand curve - Gara Afonso; Domenico Giannone; Gabriele La Spada; John C. Williams (Federal Reserve Bank of New York, 2022)
Does the federal funds rate respond to shocks when aggregate reserves are in the trillions of dollars? Has banks' demand for reserves moved over time? We provide a structural time-varying estimate of the slope of the reserve demand curve over 2010-21. We estimate a time-varying vector autoregressive model at daily frequency with an instrumental variable approach to address endogeneity. Consistent with economic theory, our estimates show a nonlinear demand function that exhibits a negative slope in 2010-11 and 2018-19 but is flat over 2012-17 and after mid-2020. We also find that the curve has moved outward, both vertically and horizontally.
Keywords: E41; E43; E52; E58; G21; 330; demand for reserves; federal funds market; monetary policy